The Social Conformity and Political Trust: Relationships with People’s Political Participation in Surabaya City - Pradika Rakasiwy, Mochamad Randy; Surya Cipta, Viona Dea (Journal of Politics and Policy, 2025)
Regional Head Elections (Pilkada) serve as a cornerstone of local democracy, reflecting citizens’ engagement beyond merely choosing leaders. This study examines the relationship between social conformity and political trust with political participation among Surabaya residents during the 2024 Pilkada. Using a quantitative correlational design, data were collected from 410 registered voters selected through judgmental sampling. Validated scales for political participation, social conformity, and political trust demonstrated satisfactory reliability (Cronbach’s alpha 0.761–0.921). Partial correlation analysis controlling for political trust showed that social conformity had a significant but low positive relationship with political participation (? = 0.265; p = 0.000). Meanwhile, when social conformity was controlled, political trust also exhibited a significant low positive correlation with political participation (? = 0.210; p = 0.000). Furthermore, multiple regression analysis with 5000-sample bootstrapping confirmed that both independent variables significantly and positively influence political participation, with political trust (B = 0.165; p = 0.000) contributing more strongly than social conformity (B = 0.122; p = 0.000). These findings highlight that while the effects are not dominant, psychosocial factors remain relevant drivers of civic engagement. The study enriches the understanding of urban political behavior in Indonesia and provides insights for designing strategies to enhance political participation through strengthening public trust and leveraging social dynamics.